A Residue Number System Based Data Hiding Using Steganography and Cryptography - Eseyin, Joseph B.; Gbolagade, Kazeem A. (NIU Journal of Social Sciences, 2019)
Cryptography and Steganography are two distinct approaches for protected data hiding and diffusion that are widely obtainable.  One hides the presence of the message and the other garbles the message.  The practices made use of information to cipher or cover their existence correspondingly. Cryptography is the science of using mathematics to encrypt and decrypt data; the data are transformed into some other gibberish form, and then the encrypted data are diffused. While Steganography is the art and science of hiding messages, steganography embeds hidden content in an unexceptional cover media to avoid spyâ€™s suspicion. In steganography the clandestine message embeds in an undisruptive looking cover such as a digital image file and the image file is transmitted.  In our proposed method, we use Steganography procedure where secret message is implanted within a hauler image file and the existence of message is hidden from the prowler. To prevent disclosure of contents of the covered file RSA algorithm is used with Steganography to enhance the sturdiness of the system. Usually in practice RSA public and private exponents are chosen to be very large this makes the decryption process slow. And to speed it up we employ the use of Chinese Remainder Theorem which concentrates on modulus calculation. This paper proposes a faster RSA-CRT algorithm for decryption of data. And by employing this technique on RSA algorithm by matching data to an image, there is less chance of an attacker being able to use steganalysis to recover data. Before hiding the data in an image, the application first encrypts it. Keywords: RSA algorithm, cryptography, steganography, LSB method, Chinese Remainder Theorem